Immunotherapy of gastrointestinal stromal tumors: current view and future directions - S. V. Boichuk; S. A. Abduraeva; P. B. Kopnin (Успехи молекулярной онкологии)
Gastrointestinal stromal tumors (GIST) are most common mesenchymal tumors in gastrointestinal tract which originate from interstitial cells of Cajal and characterized by the mutations in the KIT or PDGFRA tyrosine kinase receptors. Thus, the common therapeutic approach for GIST therapy (including metastatic, recurrent and non-resectable forms) is based on inhibiton of activities of receptor tyrosine kinases indicated above by corresponding receptor tyrosine kinase inhibitors, including first-line therapeutic agent imatinib mesylate – Gleevec. Despite of high efficacy of IM-based therapy, most of GIST patients acquire resistance to this receptor tyrosine kinase inhibitor, which in turn requires second-, third- and fourth-line therapies. The review also describes the common molecular and genetic variants of GIST and the mechanisms of primary and secondary GIST resistance to the targeted-based therapies. In addition, the role of immune microenvironment in GIST and its relationship with tumor’s mutational burden are discussed in detail, thereby illustrating the immunotherapy as one of the attractive future directions for GIST therapy. Lastly, the manuscript provides the information about the ongoing clinical trials of GIST immunotherapy.